Correction: Why Are Some Population Interventions for Diet and Obesity More Equitable and Effective Than Others? The Role of Individual Agency. - Jean Adams; Oliver Mytton; Martin White; Pablo Monsivais (PLoS Medicine)
[This corrects the article DOI: 10.1371/journal.pmed.1001990.].